THE INFLUENCE OF TEMPERATURE AND DOLOMITE ADDITION ON THE DRYING KINETICS OF SUGAR BEET PULP (BETA VULGARIS L.) - GHIRIŞAN, Adina; DRĂGAN, Simion; COŢA, Constantin; CIOICA, Nicolae; NAGY, Elena-Mihaela; MICLĂUŞ, Vasile (Studia Universitatis Babeș-Bolyai Chemia, 2018)
The aim of this study is to investigate the hot air drying kinetics of sugar beet pulp, without and with dolomite addition, in order to establish the drying mechanism. The influence of temperature and dolomite addition on the drying rates is observed. The drying constant rates and the activation energies for different working conditions are determined. The obtained results show that the drying took place in falling rate period. The obtained activation energy values correspond to the mechanism mass transfer at low amount of dolomite addition and combined mechanism, mass transformation (evaporation process) – mass transfer, at higher amount.